A new method of assessing microcirculation of the central retina in patients with different stages of diabetic macular edema in type 2 diabetes - S.A. Suk; S.Yu. Mogilevskyy; M.I. Kovtun; B.B. Zhupan (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Diabetic macular edema (DME) can develop at any stage of diabetic retinopathy, regardless of its severity. One of the triggers believed to be responsible for the accumulation of fluid in the macular area is ischemia as a frequent and severe complication of diabetic retinopathy. Optical coherence tomography angiography is a non-invasive technique that allows for visualization of retinal vascular plexus layers, quantification of microvascular parameters and correlation with functional and morphological data. Research aimed at identifying early preclinical biomarkers of microvascular abnormalities in the diabetic retina is very important, as early treatment is associated with better outcomes. The purpose is to evaluate microcirculation of the central retina in patients with different stages of diabetic macular edema in type 2 diabetes using a new method of optical coherence tomography angiography. Materials and methods. 680 patients (1296 eyes) from the Ukrainian population with type 2 diabetes mellitus and non-proliferative diabetic retinopathy were under observation. DME0 was diagnosed in 720 eyes (55.56 %), DME1 in 194 eyes (14.97 %), DME2 in 196 eyes (15.12 %), DME3 in 186 eyes (14.35 %). From this group, 477 patients (936 eyes) underwent various DME treatment according to protocols for a specific stage of edema. 203 patients (360 eyes) with DME were not treated due to their refusal, this group was the target of our study. In addition to standard ophthalmic examinations, optical coherence tomography, optical coherence tomography angiography, and computer perimetry were performed. The binarization method was used to calculate the capillary density (CD) and the area of the foveal avascular zone (FAZ). Next, an algorithm was applied to the binarized image to select pixels adjacent in color, and after counting the gray pixels, the FAZ with an area in the superficial and deep capillary plexus of the macular area was identified. The ratio of the obtained indicators of the FAZ/CD of the superficial and deep capillary plexuses was evaluated, which corresponded to the developed coefficient of microcirculation in the superficial and deep capillary plexuses of the central retina at different stages of DME. Results. During optical coherence tomography angiography at the time of admission, in 200 eyes with DME0, the average CD of superficial capillary plexus was 13.07 ± 0.60 mm2, in 54 eyes with DME1 — 11.48 ± 0.80 mm2, in 56 eyes with DME2 — 9.06 ± 0.70 mm2, in 50 eyes with DME3 — 7.45 ± 0.40 mm2. The CD of the deep plexus in DME0 was 18.59 ± 0.30 mm2, DME1 — 17.37 ± 0.40 mm2, DME2 — 15.82 ± 0.50 mm2, DME3 — 11.88 ± 1.00 mm2. When studying superficial plexus, the FAZ at DME0 was 0.45 ± 0.05 mm2, DME1 — 0.54 ± 0.04 mm2, DME2 — 0.74 ± 0.05 mm2, DME3 — 0.81 ± 0.05 mm2. During the study of the deep plexus, the FAZ in DME0 was 0.43 ± 0.03 mm2, DME1 — 0.57 ± 0.04 mm2, DME2 — 0.70 ± 0.03 mm2, DME3 — 0.75 ± 0.06 mm2. In patients with type 2 DM, the coefficient of microcirculation in the superficial capillary plexus of the central retina was significantly increased by 40 % in DME1, in DME2 by 2 times, in DME3 by 3 times compared to the control group and patients with DME0 (H = 277.47; p < 0.01). The coefficient of microcirculation in the deep capillary plexus of the central retina had a significant increase of 2 times in DME1 and 3 times in DME2 and DME3 compared to the control group and patients with DME0 (H = 320.53; p < 0.01). Conclusions. The coefficient of microcirculation in the superficial and deep capillary plexuses developed by us can be considered a prognostic marker of the microcirculation state of the central retinal zone in diabetic macular edema in patients with non-proliferative diabetic retinopathy and type 2 diabetes.